Pendampingan Pengelolaan Stok Barang dan Web Profile Pada PT. Dwi Singatama Putra - Pande Putu Gede Putra Pertama; Gede Angga Pradipta; Made Liandana; Putu Desiana Wulaning Ayu (Indonesian Journal Publisher, 2023)
PT. Dwi Singatama Putra is a company engaged in the mechanical, electrical and engineering sector, which is located in the village of Sambangan, Buleleng Regency, Bali Province. This company was founded in 2020 which is a change from UD. Triple Engineering and CV. Triple Teknik, which was previously established in 2014. This company has problems, namely: the process of recording goods in warehouses related to certain projects is still not properly recorded and even only based on goods purchase notes so that both consumables and business property are not known. exact amount. In addition, marketing is still carried out door to door to customers so that market coverage is still limited. Considering the problem, the solution that is agreed upon and offered to partners is to provide a web-based stock/warehouse system and a web application that contains information on partner profiles. In addition, partners are also given Instagram social media accounts to help market the services offered. The activities that have been carried out are training and introduction to the use of social media marketing through Instagram, managing company profiles through the website, and using the stock system. Evaluation is carried out by means of direct interviews with partners. The results of the evaluation show that service activities can provide benefits for partners.